The international approach to the control of tuberculosis - Raviglione, Mario (Henry Stewart Talks, 2013)
Burden of tuberculosis, HIV-associated tuberculosis and multidrug-resistant tuberculosis, Progress towards achievement of international targets, Challenges in 2012, Interventions needed in four areas; intensification of core tuberculosis control and care efforts, bold health policies, increased research efforts, and alleviation of socio-economic determinants of tuberculosis
Archived at 2021/11/30